2011
DOI: 10.1007/s10059-011-1038-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Duplicate Rice Sucrose Synthase Genes OsSUS5 and OsSUS7 Which Are Associated with the Plasma Membrane

Abstract: Systematic searches using the complete genome sequence of rice (Oryza sativa) identified OsSUS7, a new member of the rice sucrose synthase (OsSUS) gene family, which shows only nine single nucleotide substitutions in the OsSUS5 coding sequence. Comparative genomic analysis revealed that the synteny between OsSUS5 and OsSUS7 is conserved, and that significant numbers of transposable elements are scattered at both loci. In particular, a 17.6-kb genomic region containing transposable elements was identified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…In this regard, transcripts encoding SUS (Os03t0401300, SUS1 ; Os04t0249500, OsSUS7 ; Os03t0340500, SUS4 ) were up-regulated in Xieyou 9308 compared with the parental lines. As reported previously, OsSUS7 is highly expressed in roots [39], and SUS1 is predominantly expressed in elongating tissues, including roots where rapid formation of secondary wall takes place just after cell elongation [40]. The high level of SUS expression in Xieyou 9308 may play a major role in sink organs by providing carbon sources for sink metabolism and SUS expression may promote root elongation.…”
Section: Discussionmentioning
confidence: 74%
“…In this regard, transcripts encoding SUS (Os03t0401300, SUS1 ; Os04t0249500, OsSUS7 ; Os03t0340500, SUS4 ) were up-regulated in Xieyou 9308 compared with the parental lines. As reported previously, OsSUS7 is highly expressed in roots [39], and SUS1 is predominantly expressed in elongating tissues, including roots where rapid formation of secondary wall takes place just after cell elongation [40]. The high level of SUS expression in Xieyou 9308 may play a major role in sink organs by providing carbon sources for sink metabolism and SUS expression may promote root elongation.…”
Section: Discussionmentioning
confidence: 74%
“…Since accumulation of other carbohydrates synthesized from the UDP-glucose precursor, such as cellulose and β-glucan, were unaffected in the mutant, we suggest that the increased expression of the genes for sucrose synthase 4 and UDPase 1 may be also associated with amylopectin synthesis. Sucrose synthase 4 is suggested to be cytosolic [23] and may produce UDP-glucose, which is converted by UDPase 1 to the hexose-phosphate used for amylopectin synthesis [16]. Indeed, sucrose synthases 2 and 3 in Arabidopsis, which belong to the same group as rice sucrose synthase 4 [23], have been recently reported to direct carbon to starch synthesis [62].…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose synthase 4 is suggested to be cytosolic [23] and may produce UDP-glucose, which is converted by UDPase 1 to the hexose-phosphate used for amylopectin synthesis [16]. Indeed, sucrose synthases 2 and 3 in Arabidopsis, which belong to the same group as rice sucrose synthase 4 [23], have been recently reported to direct carbon to starch synthesis [62]. In our experiment, the elevated expression of cytosolic AGP supports that notion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the SUS genes is the starting point towards revealing their physiological roles. Presently, a number of SUS gene families have been identified in many plant species [14][15][16][17][18][19]. These studies have demonstrated that SUS genes occur as isoforms and are encoded by a small multi-gene family.…”
Section: Introductionmentioning
confidence: 99%